2009
DOI: 10.1007/s10165-009-0180-2
|View full text |Cite
|
Sign up to set email alerts
|

Extreme efficacy of intravenous immunoglobulin therapy for severe burning pain in a patient with small fiber neuropathy associated with primary Sjögren’s syndrome

Abstract: Neurological involvement occurs in approximately 20% of patients with primary Sjögren's syndrome. Although neurological symptoms can affect the peripheral nervous system and the central nervous system, the most frequent symptom is polyneuropathy. Small fiber neuropathy (SFN) is a form of painful peripheral polyneuropathy that is common in patients with diabetic neuropathy, but may also occur in toxic, infectious, or immune-mediated neuropathy. We show here a patient with Sjögren's syndrome who developed SFN an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 14 publications
1
36
1
1
Order By: Relevance
“…In general, the response to corticosteroids is poor 35,40,60,61 ; further studies are needed to assess the efficacy of immunosuppressant agents, particularly the response to Rituximab, which is a monoclonal antibody directed against CD20 antigen on B-cells. In 5 Sjögren patients treated with IvIG for a small-fiber neuropathy involving the torso as well as the proximal extremities, Morozumi et al reported improvement in pain as assessed by a visual analogue scale.…”
Section: Immunomodulatory or Immunosuppressive Therapy For Smallfibermentioning
confidence: 98%
“…In general, the response to corticosteroids is poor 35,40,60,61 ; further studies are needed to assess the efficacy of immunosuppressant agents, particularly the response to Rituximab, which is a monoclonal antibody directed against CD20 antigen on B-cells. In 5 Sjögren patients treated with IvIG for a small-fiber neuropathy involving the torso as well as the proximal extremities, Morozumi et al reported improvement in pain as assessed by a visual analogue scale.…”
Section: Immunomodulatory or Immunosuppressive Therapy For Smallfibermentioning
confidence: 98%
“…Several case reports and case series describe the efficacy of intravenous (IV) IgG in patients with peripheral neuropathy [31, 32•, 3336]. Both ataxic and painful forms of Sjögren’s-related peripheral neuropathy have benefited.…”
Section: Recent Developments In Sjögren’s Syndrome–associated Systemimentioning
confidence: 99%
“…Other therapeutic options that have shown benefit are azathioprine, methotrexate, cyclosporine, tumor necrosis factor antagonists, IVIG, and plasmapheresis. 2,4,9,21,22 Finally, rituximab shows promise as a recent therapeutic breakthrough, but its overall benefit is yet to be substantiated. 23 …”
Section: Discussionmentioning
confidence: 97%